Report of Successful Nivolumab Treatment in a Patient with Head and Neck Cancer After Allogeneic Bone Marrow Transplantation - Dong, Xiaopei; Ning Lu; Tong, Zhongsheng; Shi, Yehui (Medical Science: Trends and Innovations Vol. 7, 2025)
Head and neck squamous cell carcinoma (HNSCC) is one of the major causes of cancer-associated illness and death. HNSCC includes cancers of the oral cavity, pharynx, and larynx. Recently, programmed cell death 1(PD-1) inhibitors have shown a significant curative effect in the treatment of most solid cancers and some hematological malignancies. The effects of PD-1 inhibitors in recurrent head and neck squamous cell carcinoma (HNSCC) have also been confirmed. However, there is a lack of reliable clinical evidence to confirm the safety and efficacy of PD-1 inhibitors in patients after allogeneic hematopoietic stem cell transplantation, especially when the patient has a second primary cancer. Generally, graft-versus-host disease (GVHD) is unpredictable among these patients. The study reported the case of a patient who successfully used nivolumab without any GVHD or other immune-related adverse events for HNSCC after allogeneic bone marrow transplantation because of the Philadelphia chromosome-positive T cell acute lymphoblastic leukemia. Nivolumab, a fully human IgG4 anti–PD-1 monoclonal antibody, has shown remarkable antitumor efficacy and safety when administered to patients with recurrent HNSCC whose disease had progressed within 6 months of platinum-based chemotherapy; Furthermore, nivolumab treatment has been shown to improve the quality of life of these patients. However, little is known about the efficacy and safety of nivolumab in patients with HNSCC who have undergone allo-HSCT. This case report shows that nivolumab could be used effectively and safely in such patients, however, more clinical trials are required to confirm these results.